Growth, Instability in Production and Price Forecasting of Onion in Bangladesh - Jubayer, Md Akib; Alam, Md Akhtarul; Imam, Md Farouq; Hasan, Md Fakhrul (Journal of the Bangladesh Agricultural University, 2024)
Onion is an essential and popular spice crop which is widely cultivated and consumed in Bangladesh. Every year the country needed to import onion for fulfilling the domestic demand. Onion price has been largely influenced by import price and frequent fluctuation. The objectives of the research were to analyze the onion production behavior, instability, and forecasting of price using secondary data. The study used deterministic growth models and coefficient of variation for analyzing the growth rate and instability. Among different growth models, cubic model was identified as the best-fitted model. The average growth rate was 7.85%, and in instability analysis the coefficient of variation was 71.10%, which implies that onion production was unstable during the period of 1970-2022. Seasonal Autoregressive Integrated Moving Average (SARIMA) model was used to forecast onion price. The finding reveals that SARIMA (1, 0, 2) (1, 1, 1)12 model identified as the best model to forecast the onion price in Bangladesh. The results show that onion price followed seasonal trend, and the highest price was in October and November. These findings will support to develop appropriate policies regarding the increase of domestic supply through increased production and storage facilities, reducing post-harvest losses, and price stabilization. J Bangladesh Agril Univ 22(3): 377-385, 2024